Intraday volatility, trading volume and trading intensity in the interbank market e-MID - Markus Engler; Vahidin Jeleskovic (Philipps-University Marburg, School of Business and Economics, 2016)
We apply a multivariate multiplicative error model (MMEM) and investigate effects in the simultaneous processes of high-frequency return volatilities, trading volume, and trading intensities on the Italien Electronic Interbank Credit Market (e-MID). Analysing five minutes data from the Italian interbank market (e-MID), we found that volatilities, volumes and trading intensities on electronic Interbank Credit Market share strong causal relationship resulting in highly significant estimates of MMEM. In addition, we run several estimations to observe a change in the market behaviour of the e-MID during the last financial crisis. The main results of our study are the usability of high-frequency data models for the analysis of interbank credit market data. Moreover, we find out that changes in the market behaviour occur during the crisis. Before the financial crises, liquidity variables have a negative influence on the volatility, in contrast to the time period after the outbrake of the financial turmoil. To our best knowledge, our paper presents the first empirical application of MMEM to an interbank credit market.
Keywords: C15; C32; C52; C55; C58; E43; G01; G12; 330; multiplicative error models; interbank markets; e-MID; interstate volatility; trading intensity; intraday trading process; high-frequency financial data